2017
DOI: 10.1021/acschembio.6b01144
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Small Molecule Translesion Synthesis Inhibitors That Target the Rev1-CT/RIR Protein−Protein Interaction

Abstract: Translesion synthesis (TLS) is an important mechanism through which proliferating cells tolerate DNA damage during replication. The mutagenic Rev1/Polζ-dependent branch of TLS helps cancer cells survive first-line genotoxic chemotherapy and introduces mutations that can contribute to the acquired resistance so often observed with standard anti-cancer regimens. As such, inhibition of Rev1/Polζ-dependent TLS has recently emerged as a strategy to enhance the efficacy of first-line chemotherapy and reduce the acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 56 publications
0
82
0
Order By: Relevance
“…[14] In this study,w e generated ap harmacophore model from as mall-molecule scaffold known to disrupt the Rev1-CT/RIR PPI. We previously demonstrated that small-molecule disruptiono ft he PPI between Rev1-CT and the RIRm otif presenti nm ultiple TLS polymerases inhibits TLS in cell culture.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[14] In this study,w e generated ap harmacophore model from as mall-molecule scaffold known to disrupt the Rev1-CT/RIR PPI. We previously demonstrated that small-molecule disruptiono ft he PPI between Rev1-CT and the RIRm otif presenti nm ultiple TLS polymerases inhibits TLS in cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Compounds with IC 50 values less than 15 mm were classifieda so ur primary hits (4-11, Figure 5), while those with IC 50 values greater than 20 mm are shown in Supporting Information Table 2. [14] Compounds with IC 50 values less than 15 mm were classifieda so ur primary hits (4-11, Figure 5), while those with IC 50 values greater than 20 mm are shown in Supporting Information Table 2.…”
Section: Hit Validationmentioning
confidence: 99%
See 3 more Smart Citations